Green Economy in Sustainable Development and Improvement of Resource Efficiency - Mikhno, Inesa; Koval, Viktor; Shvets, Halyna; Garmatiuk, Oksana; Tamošiūnienė, Rima (Central European business review, 2021)
In the expansion of volumes of industrial production, there is an increase of anthropogenic influence and deterioration of the external environment that became the reason for the impossibility of a functioning market system without taking into account negative externalities. The article considers the directions and principles of a “green economy” functioning as the basis for further development of society. The current state and trends of the impact of environmental factors on other indicators of quality of life have been analysed and comparative analysis has been made on the example of developed and developing countries. Effective indices and instruments of influence on the level of ecological and economic development and main tendencies and problems arising at the introduction of “green economy”, have been considered. The use of indicators that take into account negative externalities, such as the Pigouvian tax, has been demonstrated to be more visible than widely used indices. The losses from the negative impact on the resulting economic indicators have been analysed, and a significant decrease in the per capita GDP level has been proved with the extensive development of the economy.Implications for Central European audience: This paper aims to contribute to the development of a green economy as part of a policy aimed at reducing environmental risks in the process of economic growth. The proposed indicators and tools for influencing the level of environmental and economic development arising from the implementation of the “green economy” as the main vector of sustainable development, which can be used further research and development and can be implemented by European companies.